Social Network Sites And Innovation Capabilities In The Uae Hotel Industry. Reliability And Normality Test - Al-Hammadi, Abdulhadi; Al-Hammadi, Abdulla; Al-Shami, Samer Ali Hussein; Sidek, Safiah (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The integration of information technology through social network sites in business operating and management has been recognized as one of the most resource for the development of innovation capabilities. It plays a significant role in knowledge sharing and transform which are the seeds of innovation development. The service sector is now the main domain where IT plays is extensively integrated in operation and management functions. However, the literature still lacks of clear understanding about the concept of SNSs and the innovation capabilities in hotel industry which affect the effectively use IT in their businesses. Therefore, this study aims to model SNSs and innovation capabilities. The reliability test through Cronbach alpha as well as normality tests were used.